A COMPARATIVE STUDY OF PERCEPTIONS ABOUT THE ‘COMMON EUROPEAN FRAMEWORK OF REFERENCE’ AMONG EFL TEACHERS WORKING AT STATE AND PRIVATE SCHOOLS - Burçak Yılmaz Yakışık; Fatma Ünveren Gürocak (International Online Journal of Education and Teaching, 2018)
Teachers play a vital role in the implementation of CEFR effectively. Teachers working at MONE have been offered training related to CEFR; however, not every teacher had the accessibility to the training around Turkey. That’s why, what language teachers know about CEFR and how they implement the principles of the document needs to be investigated. This study aims to find out language teachers’ views on the use of CEFR. The researchers conducted the study among English language teachers working at private and state schools in different cities around Turkey. Quantitative data analysis has been used to reveal the differences between the perceptions of English teachers regarding CEFR. The findings of the study revealed that teachers working at the private schools are more aware of the practices of the CEFR in their teaching.